The THE COUNSELING ABOUT GIVING VITAMIN A TO TODDLERS WITH IMMUNE DISORDERS - Erlina . Hayati; Stefani Anastasia Sitepu; Tetty Junita Purba; Nur Mala Sari,; Marlen Sadrina Sitepu; Husna Sari (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Vitamin A supplementation is a National Program to prevent vitamin A deficiency among Indonesian children. This program provides free vitamin A capsules to every baby and toddler who visits the Posyandu and Puskesmas. Infants aged 6-11 months are given once in February or August blue vitamin A capsules with a dose of 100,000 SI, while toddlers aged 12-59 months are given twice a year red capsules with a dose of 200,000. According to WHO, it is estimated that there are 6-7 million new cases of xerophthalmia in children under five each year, approximately 10% of whom suffer from corneal damage. Among those suffering from corneal damage 60% died within one year, while among those who lived 25% 3 million. It is estimated that at any one time as many as 3 million children were blind due to vitamin A deficiency and as many as 20-40 million suffered from a milder degree of vitamin A deficiency. The difference in mortality between children who are deficient and not deficient in vitamin A is approximately 30%. Vitamin A deficiency is estimated to affect millions of children worldwide. Approximately 250,000-500,000 children in developing countries become blind every year due to vitamin A deficiency, with the highest prevalence in Southeast Asia and Africa. Due to the high prevalence of vitamin A deficiency, WHO has implemented several initiatives for vitamin A supplementation in developing countries.